Utilizing FUCOM and AHP methods to identify the optimal beekeeping lands: A case study from Mardin, Türkiye - Çağrı Mercan; Veysi Acıbuca (PLoS ONE, 2025)
Beekeeping plays a vital role in agricultural sustainability and biodiversity conservation, yet identifying ecologically suitable areas for apiculture remains challenging. The objective of this study is to evaluate and compare two Multi-Criteria Decision-Making (MCDM) methods—the Analytical Hierarchy Process (AHP) and the Full Consistency Method (FUCOM)—within a Geographic Information Systems (GIS) framework to identify optimal beekeeping areas in Mardin Province, Türkiye. Nine environmental, climatic, topographical, logistic, and socio-economic factors were selected through literature review, legal regulations, expert consultation, and field observations. Suitability maps were generated and validated using field-verified hive locations and Receiver Operating Characteristic–Area Under the Curve (ROC–AUC) analysis. The results show that land use/cover, proximity to water sources, and precipitation were the most influential factors. Overall, 83% of hive locations coincided with areas classified as moderately suitable or higher. AHP achieved slightly higher predictive accuracy (AUC = 0.774) than FUCOM (AUC = 0.754), while FUCOM required substantially fewer pairwise comparisons, underscoring its efficiency. These findings confirm the robustness of the framework and provide a practical tool for sustainable apicultural land-use planning, offering transferable insights for policymakers, decision-makers, and beekeepers in Türkiye and other regions with similar ecological conditions.